IDENTIFIKASI RISIKO SISTEM INFORMASI BP-REMUN UNIVERSITAS LAMPUNG MENGGUNAKAN METODE NIST SP 800-30 - Aristoteles Aristoteles; Igo Febrianto; Rico Andrian; Indrianti Indrianti (Department of Computer Science, Faculty of Mathematics and Natural Sciences, University of Lampung, 2020)
The implementation of remuneration information system make a various risks that can disturb of performance assessment and make a damage for the time or material for Remuneration Management Agency of Lampung University. This research intend to analyze the risk management of remuneration information system and to know the influence of factor the implementation system of risk management remuneration information to used NIST SP 800-30 method. This remuneration information system risk management held for anticipating the source of threat by the following step risk assesment, risk mitigation, and risk evaluation. The result of this risk management is, slow system performance, no features update data, human error, no synchronization with the staffing system, password, security server, differences in perception between verifiers, no notifications data which has not been verified, late data claim and invalid report. The from risk assesment for differences in perception between verifiers and late data claim is high risk, to reduce and eliminate the impact of risk Remuneration Management Agency of of Lampung University do risk mitigation with choose verifier who masters the lecturer performance and early warning system to remind lecturers who have not made claims. The factor that influencing remuneration information system Lampung University risk assesment is human resource that having and ability in information technology for convenience support to risk all risk in every circumstances.